Experimental model to evaluate the benefits of lutein to prevent retinal phototoxicity during pars plana vitrectomy surgery using xenon source light illumination in rabbits - Teixeira, Anderson (Int J Retina Vitreous, 2019)
BACKGROUND: To evaluate the benefits of lutein in preventing retinal phototoxicity generated by xenon light sources during vitreoretinal surgery. METHODS: A prospective cross-sectional study in pigmented rabbit eyes exposed to different vitreoretinal surgery lighting simulations. Twenty Dutch-belted rabbits were divided into two groups exposed to two different xenon wavelength light sources filters (420 nm and 435 nm). In addition, two subgroups were administered with daily supplemental of 10 mg of Lutein systemically. Electroretinography (ERG), optical coherence tomography (OCT) and fluorescein angiography (FA) were performed before and after surgery to quantify the retinal damage. RESULTS: All animals submitted to the experiment presented some degree of phototoxicity independent of wavelength light filter used. Retinal damage was evident as the FA presented areas of hyperfluorescence, and the OCT depicted increased reflective areas of the inner and outer retinal layers, and RPE. ERG showed a diffuse reduction of the a and b waves amplitudes in all animals. CONCLUSION: Use of systemic administration of lutein showed no benefit to avoiding retinal phototoxicity generate to xenon light source using filters of 435 nm and 420 nm when comparing to the control group.